Ex vivo mycobacterial growth inhibition assay- re-evaluation of the tool for tuberculosis immune response and vaccine efficacy (Bangladesh Journal of Medical Microbiology, 2017)
Abstract not availableBangladesh J Med Microbiol 2017; 11 (1): 1-2